The madman's daughter - Shepherd, Megan (2013)
Dr. Moreau's daughter, Juliet, travels to her estranged father's island, only to encounter murder, medical horrors, and a love triangle
"An imprint of HarperCollins Publishers."
Keywords: Fathers and daughters -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Science fiction, American; Science fiction; Young adult fiction; Science fiction